Pelatihan Budidaya Menggunakan Media Hidroponik Pada Kelompok Wanita Tani Gundaleng Sejahtera, Sengah Temila, Kalimantan Barat - Siskariyanti, Siskariyanti; Manurung, Jack Suman Rulis; Sari, Sarita Indah; Putu Yudhia Kurniawan, Bagus; Herodemus, Herodemus; Hadi Sumitra Lada, Tri (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Plants are closely related to everyday life, especially for housewives. With the plants and environment around the house, housewives can grow plants with vegetables that are easy and not too difficult to care for, making it easy for housewives to cultivate plants using hydroponic media from simple ones to those using hydroponic display cases. The method used in this service activity does not use soil as a planting medium but is replaced by using water as a medium which contains certain nutrients and minerals to become a growing medium. Planting media. Planting using hydroponic techniques is an environmentally friendly method because the process uses natural ingredients and does not use excessive pesticides. Modern farmer with hydroponic planting system. With training on plants using hydroponic media, knowledge and experience in growing plants using hydroponic media will increase. Empowerment of the development of the use of small land to produce healthy crops for families.